Intergenerational effect on the brand preference of cosmetics in teenagers - Li, Qingshan (2013)
Our research is to investigate the degree of intergenerational effect on teenagers aged 13 to 16 years olds’ brand preferences of cosmetics products in Singapore. We explore this by first testing for the different factors that would lead to high or low intergenerational effect (knowledge of cosmetics, existing relationship with mother, existing relationship with sister). After establishing the presence of the intergenerational effect, we measured it against similarity of brand preference between mother and daughter to test for a correlation between these two elements. We did take into account two moderating factors (price and peers) that are factors likely to influence purchasing intention of buying cosmetics. Our purpose of this research is to provide relevant insights to marketers regarding how important and influential the role of mothers are in helping teenagers today shape their perceptions and preferences towards a certain cosmetic brand thus, highlighting if the marketing mix of cosmetic brands today should be directed not only towards teenagers but also to their mothers.